The Influence of Work-Life Balance and Organizational Culture on The Organizatonal Commitmen of Civil Servants at UPT Puskesmas Batang Tarang, Sanggau Regency - Sultra Tari; Arninda (www.amertainstitute.com, 2025)
This study examines how work-life balance and organizational culture influence the commitment of civil servants at the Batang Tarang Community Health Center (UPT Puskesmas) in Sanggau Regency. Using a quantitative approach, the research involved 35 respondents and applied multiple linear regression, correlation analysis, the coefficient of determination, the F-test, and the t-test. The results show the regression equation Y = 3.745 – 0.009X₁ + 0.549X₂. The correlation coefficient (R) of 0.890 indicates a very strong relationship between work-life balance, organizational culture, and organizational commitment. The coefficient of determination (R²) is also 0.890, meaning that 89% of the variation in organizational commitment is explained by these two factors, while the remaining 11% is influenced by other variables outside the study. The F-test value of 129.882 is far above the critical value of 3.29, confirming that both factors together have a significant impact. The t-test results also indicate that work-life balance (t = 7.01) and organizational culture (t = 11.155) each have a significant effect, as their t-values exceed the threshold of 2.037. in conclusion, maintaining a healthy work-life balance and fostering a strong organizational culture can significantly enhance the commitment of civil servants in the health sector.